Fabrication and oxidation resistance of the hafnium carbonitride – Silicon carbide composites. Issue 16 (15th August 2022) - Suvorova (Buinevich), V.S.; Nepapushev, A.A.; Moskovskikh, D.O.; Trusov, G.V.; Kuskov, K.V.; Kolesnikov, E.A.
Abstract: The oxidation resistance of the hafnium carbonitride Hf(C, N), HfCN+10 wt% SiC and HfCN+20 wt% SiC ceramics were investigated using thermogravimetric analysis (TGA) and static oxidation experiments at 1200 °C. TGA data showed that in the 1400 °C temperature range weight gain of the Hf(C, N)-SiC ceramics almost halted, while the Hf(C, N) sample continued to oxidize. Experiments at 1200 °C and further microstructure investigations at the ceramic/oxide interfaces showed formation of a dense HfSiO4 barrier layer with low oxygen diffusivity allowing increased oxidation resistance compared to the pure Hf(C, N). A possible formation mechanism for the protective layer and its influence on oxidation was suggested. Also, it was shown that addition of the SiC powder to the Hf(C, N) allows decreasing consolidation temperature by 200 °C without mechanical properties loss. Hf(C, N) with 20 wt% SiC showed a high fracture toughness (5.1 MPa∙m 1/2 ), high hardness (20.2 GPa), and lower density compared to the Hf(C, N) ceramics.